The Journey of Little Charlie - Curtis, Christopher Paul (New York : Scholastic Press, 2018)
When his poor sharecropper father is killed in an accident and leaves the family in debt, twelve-year-old Little Charlie agrees to accompany fearsome plantation overseer Cap'n Buck north in pursuit of people who have stolen from him; Cap'n Buck tells Little Charlie that his father's debt will be cleared when the fugitives are captured, which seems like a good deal until Little Charlie comes face-to-face with the people he is chasing.
Accelerated Reader AR
Keywords: Children of sharecroppers -- Juvenile fiction -- South Carolina; Fugitive slaves -- Juvenile fiction -- South Carolina; African Americans -- Juvenile fiction -- South Carolina; Plantation owners -- Juvenile fiction -- South Carolina; South Carolina -- Juvenile fiction -- History -- 1775-1865; United States -- Juvenile fiction -- History -- 19th century; Historical fiction